From Face-to Face to Interface: A Mixed-Methods Study of Media and Technology’s Role in Nonverbal Communication: From Face-to Face to Interface: A Mixed-Methods Study of Media and Technology’s Role in Nonverbal Communication (Sirte University Journal of Humanities, 2026)
The rapid expansion of media and technology has significantly reshaped nonverbal communication. Nonverbal communication, which includes cues such as facial expressions, gestures, posture, and tone of voice, is central to human interaction and plays an important part in conveying emotions and social meaning. However, the rise of digital communication and social media platforms has altered these dynamics, with individuals increasingly relying on written text and emoticons to convey messages. The aim of this study is to investigate how the use of media and technology affects the use of nonverbal cues within the broader framework of Computer Mediated Communication (CMC). Twenty Libyan English postgraduate students from the Faculty of Languages at the University of Benghazi participated in this study. A mixed-method design combining survey data and semi structured interviews was employed to collect and analyse evidence. Findings revealed that whilst students continue to value traditional nonverbal communication in face-to-face contexts, they increasingly practice communicative choices that allow them to adapt to digital substitutes such as emojis, memes, GIFs, and textual markers, reflecting both a transformation and a partial loss in nuance in nonverbal expression.
Keywords: verbal communication; nonverbal; communication; CMC